Effects of V content on the microstructure and mechanical properties of Nb31Ti37-xZr26Al6Vx refractory medium-entropy alloys. (April 2022) - Huang, R.; Tan, J.; Li, W.; Dong, Q.; Li, C.J.; Qin, X.M.; Guo, S.F.; Lu, Y.P.
Abstract: Most refractory complex concentrated alloys (CCAs) exhibit limited plasticity and high density, which greatly limits their large-scale applications. To address these issues, a series of Nb31 Ti37- x Zr26 Al6 V x ( x  = 3, 5, 7, 9, and 11 at. %) refractory medium-entropy alloys (RMEAs) were designed and prepared in this work with the help of phase diagram calculation software. The synergistic effects of V and Ti on the microstructure, mechanical properties, and strengthening mechanisms of Nb31 Ti37- x Zr26 Al6 V x RMEAs are investigated in detail. Compared with the reported CCAs with limited plasticity and high density, our alloys with a single BCC structure offer excellent compressive plasticity greater than 50% at room temperature and a lower density less than 6.4 g/cm 3 . Alloys have higher yield strength at room temperature with the increasing content of V. The high yield strength of alloys primarily originates from the inherent yield strength of the alloy's components and the solution strengthening resulting from the lattice distortion. The alloys studied in this work provide evidence that the high-strength RMEAs with excellent plasticity can be obtained through careful composition design. Graphical abstract: Image 1 Highlights: Nb31 Ti37- x Zr26 Al6 V x ( x  = 3–11 at. %) RMEAs are designed and prepared. The RMEAs have good ductility, low density, and high specific strength. The strength of RMEAs increases with increasing V content at high temperature. Solution strengthening is the main strengthening mechanism in these alloys.